CRISPR/Cas9-mediated editing of the TM6 MADS-box gene in the octoploid strawberry (Fragaria × ananassa) - Martín-Pizarro, Carmen (My University, 2019)
The B-class of MADS-box transcription factors has been studied in many plant species, but remain uncharacterized in Rosaceae. APETALA3 (AP3) is a member of this family, controlling petal and stamen identities in Arabidopsis. In this study, we have identified two members of the AP3 linage in Fragaria × ananassa: FaAP3 and FaTM6. Interestingly, FaTM6, and not FaAP3, shows an expression pattern equivalent to that of AP3 in Arabidopsis. CRISPR/Cas9 system is becoming a robust tool for targeted and stable mutagenesis of DNA. In this work, we have used this genome editing system for the first time in an octoploid species in order to study the function of TM6 in strawberry flower development.
Keywords: Fresas; Strawberry; Fragaria x ananassa; CRISPR/Cas9; Flower; Stamen; Petal; TM6; AP3